The Process of Becoming a Teacher as Viewed by Mentors and Will-be Teachers - Huszti Ilona; Густі Ілона (Valerij Padjak-II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2013)
Abstract. The research detailed in the present article has provided insights into the opinions of school mentors and will-be teachers about the process of becoming a teacher. An attempt has been made to clash the various opinions and to clarify what type of help trainee teachers require from the mentors and what kind of support the mentors give to will-be teachers during their teaching practice at the school. The terms practice teacher, trainee teacher and will-be teacher are used interchangeably to refer to one and the same person, i.e. 4th or 5th year college student doing their compulsory teaching practice in a primary or secondary school. The terms mentor, cooperative teacher and subject teacher also refer to the same person in this study, namely the person who is responsible for and gives most support to practice teachers during the teaching practice, provides them with useful advice and suggestions how to design and give lessons.
Процес становлення вчителя під опікою наставника
https://opac3.brff.monguz.hu:443/hu/record/-/record/157029
https://www.kmf.uz.ua/hun114/letoltes/acta/ActaAcBereg2013_2.pdf
Keywords: will-be teachers; mentors; becoming teacher